PREDIKSI JUMLAH ACTUAL STOCK PADA PRODUKSI SARUNG TANGAN MENGGUNAKAN METODE FUZZY MAMDANI - Utari, Cut Try (Riau Journal Of Computer Science, 2020)
To fulfill every consumer demand, the company must ensure that production activities run well. However, continuous production activities, sometimes making the facilities used especially production machines, do not always function properly.Â Damage to the machine can hamper the production process which results in the amount of production not being metÂ which effecting in unmet amount of production so the production process of goods experiencing delays (downtime). There are uncertainties in downtime and stock requirements so in this case fuzzy is applied to predict the amount of actual stock production. And in this study Fuzzy Mamdani has been able to produce a prediction of Actual Stock